Influence of aquatic exercise training on balance in young adults - Luana Mann; Julio Francisco Kleinpaul; Carlos Bolli Mota; Saray Giovana dos Santos
Introduction Physical exercise programs have been suggested to soften or reverse balance deficits and postural deviation. Objective This study investigated the influence of a systematic aquatic exercise program on body balance. Method Healthy young adult volunteers of both genders, aged 18-30 years were assessed. The experimental group (EG, n = 20) was subjected to 24 sessions of aquatic exercises of 50 minutes long, performed three times a week, and the control group (CG, n = 25) suffered no intervention. A 3-D force platform was used to calculate the center of pressure displacement (COP) in anteroposterior and mid-lateral directions with or without visual information. The individuals were assessed in pre or post-training. Results The results demonstrated a decrease in body oscillation in both visual conditions, with post-training values lower than pre-training ones. Visual information was not expressive for EG post-training. Conclusion It was concluded that the program was effective for body balance improvement.